Praktik Personal Branding Notaris terhadap Batasan, Etika dan Legalitasnya ditinjau dari Undang-Undang Jabatan Notaris dan Kode Etik Notaris: Notary Personal Branding Practices in Relation to Their Limitations, Ethics, and Legality as Reviewed from the Notary Position Law and Notary Code of Ethics - Kurniawan, Arie; Hartanto, Farrel Billie Akmal Fahar Ary; Dewantary, Ariska (Perspektif Hukum, 2025)
Personal branding, understood as the reputation or "self-brand" of an individual, has become an important concept in professional practice. In the context of notarial practice in Indonesia, efforts to develop personal branding must be carefully balanced against strict legal and ethical constraints. This paper analyzes the practice of personal branding by Indonesian notaries in light of the Notary Position Law (Undang-Undang Jabatan Notaris, UUJN) and the Notary Code of Ethics. Using a normative legal research method with a statute approach and examination of professional ethics, this study reviews relevant regulations, ethical guidelines, and comparative international practices. The findings indicate that while notaries may engage in certain reputational activities such as legal education or informational outreach, direct self-promotion is prohibited. Article 15 paragraph (2) letter e of the Notary Position Law explicitly grants the authority to provide legal counseling which can enhance reputation, but Article 4 paragraph (3) of the Notary Code of Ethics forbids any form of advertising or personal publicity. International comparisons from Spain and France reveal similarly restrictive rules for notary advertising. In conclusion, Indonesian notaries must perform personal branding within the narrow confines allowed by law and ethics, emphasizing professional expertise and public education while avoiding any media-based promotion of their notarial status. These findings aim to guide notaries in promoting their professional image without violating legal or ethical boundaries.